Structural, mechanical and bioactivity properties of SiO2-CaO-B2O3-Na2O-P2O5-CaF2 glass and glass-ceramics utilized eggshell as calcium source - Loh, Zhi Wei (2024)
As humans age, the deterioration of teeth in adults and even children are unprotected and easy to fracture due to the loss of mechanical strength over time. Hence, biomaterials such as bioactive glasses have gained significant scientific interest from researchers for application in dentistry. In the present work, the bioactive glass was synthesized through a melt-quenching approach with the configuration of 45SiO2– 25CaO–10B2O3–10Na2O–(10–x)P2O5–xCaF2, where x = 0, 2, 4, 6, 8 and 10 wt.%. The eggshell waste was chosen as the calcium source. Considering the intrinsic brittleness of the glass, heat treatment is performed to improve the mechanical properties of the bioactive glass. Meanwhile, both samples will be immersed in phosphate buffer saline for 7 and 14 days to evaluate their bioactivity and biodegradability properties. Among the samples, BG3F with a CaF2/P2O5 ratio of 6/4 demonstrated the optimal performance based on the structural, mechanical, bioactivity and biodegradability properties. The density of BG3F showed increment with heat treatment temperature, reaching a maximum value of 2.626 g/cm3 at a temperature of 700 °C. X-ray diffraction analysis revealed the phase formation of fluorapatite, wollastonite, and cuspidine in the BG3F samples after heat treatment. In terms of mechanical results, BG3F heat-treated at 700 °C revealed the highest microhardness range of 6.72 GPa to 6.95 GPa and fracture toughness of 3.55 MPa·m1/2 to 3.62 MPa·m1/2 after 14 days of immersion. Furthermore, the pH of the glass and glass-ceramics samples showed an increasing trend ranging from 7.437 to 9.636 and 7.437 to 8.217, respectively, after being immersed for 14 days, indicating their bioactivity in response to the immersion medium. In conclusion, the BG3F sample with a heat treatment of 700 °C revealed the optimum performance, demonstrating the highest mechanical properties while maintaining bioactivity and biodegradability. The microhardness of the studied samples is comparable to the human enamel (2.00 – 5.00 GPa) and the commercial dental glass-ceramics (4.00 – 6.50 GPa) by more than 39% and 6.92%, respectively. Therefore, this research contributes to a novel approach by using wastes in fabricating bioactive glass while improving the mechanical properties of glass-ceramics for dental applications.